Ventilating cities : Air-flow criteria for healthy and comfortable urban living - Kato, Shinsuke (Springer Geography, 2012)
The majority of the world's population live in environments with artificially weakened wind as buildings in urban areas form wind-breaks and reduce wind speeds. Anthropogenic heat is also generated and during the summer dense urban areas suffer from the urban heat island effect, a known urban climate problem. This book discusses how to evaluate the urban wind environment, including ventilation performance and thermal comfort. This book is organized in two parts; Wind Environment and the Urban Environment and Criteria for Assessing Breeze Environments. It includes chapters on sea breeze in urban areas; thermal adaptation and the effect of wind on thermal comfort;  health risk of exposures; pollutant transport in dense urban areas;  legal regulations for urban ventilation and new criteria for assessing the local wind environment. Keywords: urban wind environments, urban heat island, urban climate, land use change, thermal comfort, risk assessment, urban air pollution, urban ventilation